2011
DOI: 10.2113/jeeg16.4.145
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeophysical Investigations at Hidden Dam, Raymond, California

Abstract: Self-potential and direct current resistivity surveys are carried out at the Hidden Dam site in Raymond, California to assess present-day seepage patterns and better understand the hydrogeologic mechanisms that likely influence seepage. Numerical modeling is utilized in conjunction with the geophysical measurements to predict variably-saturated flow through typical two-dimensional dam cross-sections as a function of reservoir elevation. Several different flow scenarios are investigated based on the known hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Others, like Mydlikovski et al (2007) used high-frequency electromagnetic methods: The depth of penetration of electromagnetic waves was small due to the fact that, in this medium, electromagnetic waves are strongly attenuated, and the structural weaknesses of levee caused by high level of ground water is characterised by high level of electrical permittivity and low resistivity. For fast detection of seepage inside embankments, the self-potential (SP) technique has been the preferred one (Rittgers et al 2015;Bolève et al 2011;Minsley et al 2011), and salt tracers injection have also been used with SP to enhance the detection of preferential flow path in heterogeneous media (Ikard et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Others, like Mydlikovski et al (2007) used high-frequency electromagnetic methods: The depth of penetration of electromagnetic waves was small due to the fact that, in this medium, electromagnetic waves are strongly attenuated, and the structural weaknesses of levee caused by high level of ground water is characterised by high level of electrical permittivity and low resistivity. For fast detection of seepage inside embankments, the self-potential (SP) technique has been the preferred one (Rittgers et al 2015;Bolève et al 2011;Minsley et al 2011), and salt tracers injection have also been used with SP to enhance the detection of preferential flow path in heterogeneous media (Ikard et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Malinverno (2002) and Sambridge and others (2006) has been adapted to perform model assessment FDEM geophysical datasets using a trans-dimensional Bayesian MCMC algorithm, the details of which can be found in Minsley (2011). This is a one-dimensional algorithm that produces an ensemble of many (tens to hundreds of thousands) layered-earth models of electrical resistivity as a function of depth that are consistent with the measured data.…”
Section: Introductionmentioning
confidence: 99%
“…Making proposals that efficiently explore the space of plausible models is extremely important and is discussed in detail by Minsley (2011). The algorithm runs for a prespecified number of samples are drawn or until some convergence criterion is met.…”
Section: Introductionmentioning
confidence: 99%
“…In karstic areas, the SP data have been used to locate the preferential flow pathways due to the presence of sinkholes and crypto-sinkholes (Jardani et al, 2006a). Minsley et al (2011) demonstrated its efficiency to detect leakages in earth dams. In geothermal systems, the self potential anomalies can amount hundreds of millivolts and can be used to reconstruct the large-scale pattern of ground water flow (Ishido, 1989;Revil and Pezard, 1998).…”
Section: Introductionmentioning
confidence: 99%